Periodisasi Masa Remaja dan Ciri Khasnya; Pubertas, Remaja Awal dan Remaja Akhir - Sholin, Aribah; Nasution, Abdillah; Fitrah, Aidil; Nazhira, Najwa; Syafitri, Nur Indah; Ulayya, Salsabil Beli; Lubis, Ramadan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Adolescence is a time of biological, cognitive, and socioemotional changes that occur throughout the developmental transition from childhood to adulthood. Teenagers' primary responsibility is getting ready to become adults. The periodization of adolescence, from early to late, is the subject of this article, which focuses on the development of the mind, the emotions, and the social and moral aspects of life. In order to help, comprehend, and encourage teenagers who are beginning the puberty period of their development, parents' and educators' roles are crucial in this process. Qualitative approaches were used in this study. In qualitative research, images, videos, interviews, and other media are used as data sources. Information gleaned from the interview process is provided as descriptions using simple-to-understand language to comprehend. In addition, there is supporting documentation in the form of images taken during observations and interviews. Purposive sampling, or sampling done in accordance with predetermined goals or considerations, is the method used in this study.